Mammary myoid hamartomas: reports of two cases and a review of the literature - Xia, Tian (Int J Clin Exp Pathol, 2019)
The purpose of this report is to determine the clinicopathological and immuno-phenotypical characteristics of myoid hamartoma of the breast (MHB). The clinical data, histological morphology, and immunohistochemical results of 2 patients diagnosed with MHB were analyzed, and 15 cases of MHB reported in China were reviewed. Both patients were female, aged 28 and 35 years old, and their lesions were located in the upper outer quadrant of the left breast and the right breast respectively. The lesions measured 3 cm × 3 cm × 2.5 cm and 6.5 cm × 6 cm × 4.5 cm. A gross examination indicated a grayish solid block with clear boundaries. A microscopic examination showed different proportions of ducts and acini, beam myoid cells, adipose tissue, and fibrous stroma. The myoid cell bundles of both specimens were positive for vimentin, SMA, h-caldesmon and desmin, but negative for ER, PR, PCK, s-100, Calponin, and P63. Both cases were confirmed as MHB based on their clinical, histological and immuno-phenotypical characteristics. Our findings provide further insights into the pathological basis of MHB, which can help avoid both misdiagnosis and missed diagnosis.